Label‐Free Photonic Biosensors: Key Technologies for Precision Diagnostics - Maria Soler; Laura M. Lechuga (ChemistryEurope)
With the rise of multidrug‐resistant pathogens, emerging zoonotic viruses, and the increasing prevalence of cancer, the modernization of clinical diagnostics has become a critical priority. Label‐free optical biosensors, including those based on plasmonics and silicon photonic technologies, offer promising solutions for highly sensitive molecular analysis, rapid assay times, and decentralized operation. However, important challenges must be addressed for their successful clinical implementation, including the miniaturization and integration in compact, automated devices and the direct analysis of complex human specimens, like blood. In this context, an overview of recent advancements and future perspectives in photonic biosensors are provided for clinical diagnostics. The critical limitations of these technologies are examined, and specific research objectives that need to be met to fully leverage the potential of photonic biosensors and accelerate their adoption in the clinical practice are proposed. Finally, the most innovative biosensor designs and methodologies are highlighted, along with their prospects for contributing to precision diagnosis and personalized medicine.